Insect PRXamides: Evolutionary Divergence, Novelty, and Loss in a Conserved Neuropeptide System. Issue 1 (20th January 2023) - Farris, Sarah M
Abstract: The PRXamide neuropeptides have been described in both protostome and deuterostome species, including all major groups of the Panarthropoda. Best studied are the insect PRXamides consisting of three genes: pk/pban, capa, and eth, each encoding multiple short peptides that are cleaved post-translationally. Comparisons of genome and transcriptome sequences reveal that while retaining its fundamental ancestral organization, the products of the pk/pban gene have undergone significant change in the insect Order Diptera. Basal dipteran pk/pban genes are much like those of other holometabolous insects, while more crown species have lost two peptide coding sequences including the otherwise ubiquitous pheromone biosynthesis activating neuropeptide (PBAN). In the genomic model species Drosophila melanogaster, one of the remaining peptides (hugin) plays a potentially novel role in feeding and locomotor regulation tied to circadian rhythms. Comparison of peptide coding sequences of pk/pban across the Diptera pinpoints the acquisition or loss of the hugin and PBAN peptide sequences respectively, and provides clues to associated changes in life history, physiology, and/or behavior. Interestingly, the neural circuitry underlying pk/pban function is highly conserved across the insects regardless of the composition of the pk/pban gene. The rapid evolution and diversification of the Diptera provide many instances of adaptive novelties from genes to behavior that can be placed in the context of emerging selective pressures at key points in their phylogeny; further study of changing functional roles of pk/pban may then be facilitated by the high-resolution genetic tools available in Drosophila melanogaster .